2020
DOI: 10.1002/fsn3.1997
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Propolis: Ultrasound‐assisted enhanced ethanolic extraction, volatile components analysis, antioxidant and antibacterial activity comparison

Abstract: This study was aimed to enhance the extraction yield of propolis samples using ultrasound technology, analyze the volatile compounds, and compare the antioxidant and antimicrobial effect of propolis extracts of different areas. Four propolis samples were collected from different regions of China, namely: Linqing, Shandong Province (LSP); Yingchun, Heilongjiang Province (YHP); Changge, Henan Province (CHP); and Raohe, Heilongjiang Province (RHP). The ultrasound extracts of CHP and RHP showed a higher total phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
4
16
3
Order By: Relevance
“…The result of the optimized value of TPC (192 mg GAE/g) was important in comparison with that obtained by ultrasoundassisted extraction from Malaysian propolis, which the predicted value of 162.46 mg GAEq/g [48], which was more important than Lithuanian propolis extract obtained by traditional extraction methods [49]. Besides, it was similar to those obtained by the same extraction method for Chinese propolis, where the TPC range was from 166 to 201.07 mgQEq/g [50].…”
Section: Effect Of Operating Conditions On the Tpc Responsesupporting
confidence: 62%
“…The result of the optimized value of TPC (192 mg GAE/g) was important in comparison with that obtained by ultrasoundassisted extraction from Malaysian propolis, which the predicted value of 162.46 mg GAEq/g [48], which was more important than Lithuanian propolis extract obtained by traditional extraction methods [49]. Besides, it was similar to those obtained by the same extraction method for Chinese propolis, where the TPC range was from 166 to 201.07 mgQEq/g [50].…”
Section: Effect Of Operating Conditions On the Tpc Responsesupporting
confidence: 62%
“…Since the 35:1 (v:w) liquid:solid ratio led to an extract having 2417 μmol TEAC/g propolis, it is reasonable to explain these punctual differences by the operation conditions (more liquid phase, 28 W/L ultrasonic bath), source of propolis and US field topology. Ding et al [45] determined a range of variation from 36.8 to 106.7 µmol TEAC/g of extract, different from the present study, 2.2 – 1030 µmol TEAC/g propolis. The difference is not unexpected considering the source of propolis (Chinese against Romanian), solvent (70 % ethanol against 0, 25 % and 50 % ethanol), and US bath characteristics (220 W, 40 kHz, 30 min against 110 W, 40 kHz, 10 – 100 min).…”
Section: Resultscontrasting
confidence: 96%
“…The propolis extract (P1) collected from Ziarat region expressed maximum flavonoid content (0.6586 ± 0.329) and the extract (P6) from Bela region have the lowest content (0.1546 ± 0.087) mg of quercetin g −1 of propolis extract presented in ( Table 2 ). Results of current study are minimum than other reported studies from different location in Turkey [ 3 ], Pakistan [ 1 ], China [ 21 ], and Iran [ 22 ]. According to Choi et al [ 20 ], the variations in total phenolic and total flavonoids of propolis samples depend on their geographic origin.…”
Section: Discussioncontrasting
confidence: 85%